HUBUNGAN RESILIENCE AT WORK DENGAN KINERJA MARKETING OFFICER DI PT X - Prithasari Kusumaputri; Benedicta Prihatin Dwi Riyanti (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2018)
Marketing is an important part in finance companies. With the nature of their work, they required to show good performance so that resilient employees are keen to show more optimal effort. This research includes applied research with mixed method approach. Researchers used McEwen (2011) theory to created resilience measure and secondary data for employee performance. By using spearman correlation, the result showed that is no relationship between the two variables. In general, the resilience variables were in the moderate category (52,1%) and the performance variables were in exceptionally high category (36,8%). From the result, the development program recommended is to provide intervention for employees whose performance is still relatively moderate. Based on interviews, the constraines are giving and getting information, and difficulties to deal with dealers and consumers. Therefore, it is necessary to provide salesmanship training that focuses on communication skills.